Construction of Mathematical Start-Up Business Index Formulation for Swiftlet Ranching Industry in Malaysia (Contemporary Mathematics, 2023)
An important agricultural product exported by Malaysia is swiftlet nests. Due to its high demand many entrepreneurs venture in this industry. Hence with the bioactive ingredients and dietary values are significant in support the manufacture of medicines in EBN. However, there are a lot of entrepreneurs who unable to fulfill the request of EBN production and failed in this industry. To prevent failure in the birds' nest swiftlet ranching industry, a mathematical modelling formulation should be developed. Thus, the purpose of the research is to construct a general formulation of the start-up business index equation for the swiftlet ranching industry in Malaysia. Experts interviewed found that there were eight factors of starting a business that mattered. Based on the findings, the weightage of the start-up business factors has been used in constructing the general formulation of start-up business index function of the swiftlet ranching industry in Malaysia. Hence, we will develop the system of start-up business factors in the swiftlet birds nest ranching industry using the general formulation of the start-up business index equation.
Keywords: general formulation; start-up business index equation; swiftlet ranching industry; health food product